Analisis Sistem Manajemen SDM Pada Rekrutmen Karyawan (Studi Kasus Karyawan CV. New KMU Slawi Kota Tegal) - Anisa Ifadah; Aida Fathonah; Aqidatul Latifani (Journal of Southeast Asian Islam and Society, 2022)
This study discusses the recruitment and selection of employees on the CV. New KMU Slawi Tegal City. This study aims to analyze the employee recruitment and selection process whether transparency or not. The research method used is qualitative. This research proves that the process of recruitment and selection of employees is carried out transparently and in accordance with the theory of Human Resource Management. As for the implications of this research, the company is expected to always carry out evaluations starting from planning the recruitment deadline to evaluating employee salaries, the aim is that employees always have loyalty, morale, and a high work ethic to the company and also as a form of preventing high employee turnover in the company.